Cancer genetic counseling in Chile: Addressing barriers, confronting challenges, and seizing opportunities in an underserved Latin American Community - Ricardo Fernández-Ramires; Sebastián Morales-Pison; Guilherme Gischkow Rucatti; César Echeverría; Esteban San Martín; Francisco Cammarata-Scalisi; Alexis Salas-Burgos; Daniela Adorno-Farias; Wilfredo Alejandro González-Arriagada; Yolanda Espinosa-Parrilla; Daniela Zapata-Contreras; Gabriela Norese; et al. (Genetics in Medicine Open)
Purpose: Despite the rapid advancements in genomics and the enactment of a new cancer law in Chile, the implementation of cancer genetic counseling continues to face significant challenges because of limited resources and infrastructure. Methods: We conducted a survey targeting health care providers who offer genetic counseling to patients with cancer and possess training in genetics and counseling. Additionally, we distributed a separate survey to high-risk patients associated with an advocacy group to gather insights on their perceptions of and experiences with cancer genetic counseling. Results: Among the surveyed providers, 21% were nonmedical professionals who developed their skills through postgraduate continuing education programs. Germline testing was not performed in 47% of cases. Among the participants, 37% considered genetic counseling important for understanding the cause of their cancer, 25% valued knowing their risk of developing future tumors, and 33% believed it would benefit their current cancer treatment. Just over half of the patients (54%) had access to genetic counseling. Among those that received genetic counseling, 85% found it beneficial. Conclusion: In Chile, barriers to genetic counseling persist, particularly in rural areas and because of a shortage of trained professionals. Public policies recognizing genetic counseling’s importance are crucial, along with expanding training and infrastructure. Understanding patient perceptions and increasing the number of trained genetic counseling into cancer care, educating clinicians, and advocating for increased access are key steps for enhancing cancer treatment effectiveness in Chile.